Konsep ‘Dunia Kotak’ dalam Perspektif Pendidikan Agama Islam: Analisis Sosial dan Budaya Digital - Muhammad; Musa Asy’arie; Mahasri Shobahiya (Medan Resource Center, 2025)
The development of human civilization reflects a shifting worldview—from flat-earth beliefs to a spherical understanding of the planet, and now to the phenomenon of the “boxed world.” The concept of the “boxed world” refers to a modern pattern of life structured within rigid physical, social, digital, and cognitive frameworks characterized by segmentation and categorical thinking. This study aims to analyze the concept of the “boxed world” from the perspective of Islamic Religious Education (Pendidikan Agama Islam/PAI) and to explore its social and digital-cultural implications. Using a thematic-conceptual approach, the findings reveal that the “box” metaphor extends beyond architectural design to shape social systems, digital behavior, and modern patterns of thought. The rise of social polarization and the pursuit of efficiency in modern society have fostered “boxed thinking,” which tends to weaken critical reflection, creativity, and spirituality. The novelty of this study lies in integrating the metaphorical analysis of the “boxed world” with core values of Islamic Religious Education as an ethical-normative framework for responding to digital culture. From an Islamic perspective, foundational values such as tawhid (divine unity), ukhuwah (brotherhood), justice, trustworthiness (amanah), and balance (tawazun) function as guiding principles to ensure that digital transformation and social structures remain aligned with human dignity and spiritual equilibrium.